Environmental Impact of Treatment of Pharmaceutical Packaging Materials - Li, Jiayang (International Journal of Natural Resources and Environmental Studies, 2024)
In this paper, LCA method is used to explore how a certain material or a specific drug packaging waste enters the environment after different garbage disposal methods, and what impact it has on the population and community after entering the environment. Pharmaceutical packaging materials are unavoidable in human life a class of materials, the international market for product packaging increasingly strict environmental requirements, China’s drug manufacturers and pharmaceutical packaging industry put forward more severe requirements, in such a situation, the drug packaging to achieve effective recycling and pollution prevention is China’s drug manufacturers must face the problem. The domestic research direction is mainly LCA, and the development and application of green packaging materials and new pharmaceutical packaging materials. The international research also includes carbon footprint estimation and LCM of pharmaceutical packaging, as well as innovation in recycling technology.